Book review: John Chambers and Diane Brady. Connecting the Dots: Lessons for Leadership in a Start-up World. (September 2021) - Arora, Ajay
John Chambers and Diane Brady. Connecting the Dots: Lessons for Leadership in a Start-up World, Harper Collins Publishers, 2018, 320 pp.